Correction: Tetraaryl pyrenes: photophysical properties, computational studies, crystal structures, and application in OLEDs. Issue 14 (9th February 2016) - El-Assaad, Tarek H.; Auer, Manuel; Castañeda, Raul; Hallal, Kassem M.; Jradi, Fadi M.; Mosca, Lorenzo; Khnayzer, Rony S.; Patra, Digambara; Timofeeva, Tatiana V.; Brédas, Jean-Luc; List-Kratochvil, Emil J. W.; Wex, Brigitte; et al.
Abstract : Correction for 'Tetraaryl pyrenes: photophysical properties, computational studies, crystal structures, and application in OLEDs' by Tarek H. El-Assaad et al., J. Mater. Chem. C, 2016, DOI: ; 10.1039/c5tc02849c .